Pengaruh lingkungan kerja terhadap kinerja karyawan bagian servis pada PT. Agung Toyota SM. Amin Pekanbaru - Tika Putri; Annisa Mardatillah (Pelantar Press, 2022)
This research was conducted by the author aims to determine the effect of the work environment on the performance of service employees at PT. Agung Toyota SM. Amin Pekanbaru. This study is to determine the dimensions of the work environment that have the most influence on employee performance. The indicators of the work environment used in this study are the physical environment and the psychological environment, as well as the employee performance indicators used in this study, namely the quantity of work, quality of work, and timeliness. Sampling using saturated sampling method for employees and for leaders using purposive. The data in this study were obtained through questionnaires, and the data analysis used was simple regression analysis with the SPSS v.23 application. In the overall validity test, the statement items are declared valid. Result show work environment influence to employee environment.